Standards proposals of nursing the patient undergoing percutaneus coronary diagnosticks and intervention - Dzik, Małgorzata; Klamut, Henryka; Krupienicz, Krupienicz (Nursing in the 21st Century, 2012)
STANDARDS PROPOSALS OF NURSING THE PATIENT UNDERGOING PERCUTANEUS CORONARY DIAGNOSTICKS AND INTERVENTIONThe aim of this paper is to present proposal of three nursing standards. First – patient undergoing coronarography or PCI in planned mode. Second – patient with ACS undergoing primary percutaneus coronary intervention and third – patient in Cardiological Ward after invasive procedures.Coronary Artery Disease and Acute Coronary Syndroms are the main diagnosis in Cardiology Wards nowdays and the number of these patients in hospitals grows rapidly. Invasive intervention may results in several complications, sometimes life threatening. Thus, to define and follow standards is what warrants professional care and safety.